Transformasi Ruang Publik Digital: Studi Kasus Komentar Netizen dalam Akun Curhat - Sekar Kasih, Arum Rindu; Maharani, Tisa (Kajian Linguistik dan Sastra, 2024)
In the current era of digital technology, the various digital platforms available in the form of social media mean that anyone can express as many things as they wish. Social media seems to be a personal "journal" but can be connected to the virtual world community or netizens so that netizens can also monitor the social media activities of each individual. One of the uses of social media by netizens is as a place to "talk" and respond to each other. These netizens do not know each other personally in the digital space. Uniquely, they do not hesitate to express personal experiences, then netizens respond ideally when the speaker and the interlocutor communicate directly. Cermin Lelaki's Instagram account presents a social media concept that is used as a forum for receiving men's conversations with various life problems. The story was then shared with the public and received many comments from netizens. Using the method of observing the language interactions of netizen comments on the Cermin Lelaki account, this research aims to explore netizen comments in response to venting and explore the extent to which the existence of digital public space can shape configurations or patterns of language activity from netizen comments. Language activities in netizen interactions are influenced by many underlying factors.